1959
DOI: 10.1002/zaac.19593000509
|View full text |Cite
|
Sign up to set email alerts
|

Die Basenreaktionen der Hexacarbonyle der Chromgruppe. II. Über die Basenreaktion des Molybdänhexacarbonyls

Abstract: Die Basenreaktion des Molybdänhexacarbonyls führt unter Verwendung von alkoholischen Kalilaugen bei höherer Temperatur zu 2kernigen Hexacarbonyl‐m̈‐trioldimolybdaten(0), wobei im Falle des aus Methanol anfallenden Produktes eine OH‐Gruppe durch OCH3 ersetzt ist. Die Reaktion spielt sich zum Unterschied von derjenigen des Cr(CO)6 ohne Wasserstoffentbindung ab und stellt somit eine reine Substitutionsreaktion dar; das CO reagiert wiederum unter Formiatbildung. Durch Fällungsreaktionen, Leitfähigkeit, IR‐Spektren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1960
1960
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…The authors argued that the location of the hydrido ligand is indicated by the opening of one of the C−W−C bond angles and that each W is better described as being heptacoordinated, with the geometry of a trigonal pyramid and a square pyramid sharing an apex . A small tungsten hydroxocarbonyl cluster of the type K 3 [W 2 (OH) 3 (CO) 6 ] was prepared from the alkaline hydrolysis of the hexacarbonyls, W(CO) 6 .…”
Section: 3 Tungstenmentioning
confidence: 99%
“…The authors argued that the location of the hydrido ligand is indicated by the opening of one of the C−W−C bond angles and that each W is better described as being heptacoordinated, with the geometry of a trigonal pyramid and a square pyramid sharing an apex . A small tungsten hydroxocarbonyl cluster of the type K 3 [W 2 (OH) 3 (CO) 6 ] was prepared from the alkaline hydrolysis of the hexacarbonyls, W(CO) 6 .…”
Section: 3 Tungstenmentioning
confidence: 99%
“…IR spectroscopic data for [M(CO) 5 F] - species were reported in the 1970s, but recent studies by Darensbourg and co-workers suggest that [W(CO) 5 F] - , at least, is only stable under an atmosphere of CO . Removal of CO results in the reversible formation of a triply bridged fluoride dimer: Analogous [M(CO) 5 OH] - species also lose CO in a similar fashion and have been reported to form either dimers (M = Mo, W) or tetramers (M = Cr, Mo, W) . [W(CO) 5 OR] - species (R = H, CH 3 14 ) have been characterized in solution by IR spectroscopy, and a crystal structure of [W(CO) 5 OPh] - has been published .…”
Section: Introductionmentioning
confidence: 99%
“…During these experiments, DMSO was considered beneficial and the title complex fac-[Mo(CO) 3 (DMSO) 3 ] was prepared and crystallized. This complex was first reported in the literature in 1959 (Hieber et al, 1959), but its crystal structure remained, apparently, elusive to date. Notably, it also appears that since then the complex has never been mentioned again.…”
Section: Chemical Contextmentioning
confidence: 97%